2008
DOI: 10.1038/ng.91
|View full text |Cite
|
Sign up to set email alerts
|

Multiple loci identified in a genome-wide association study of prostate cancer

Abstract: We followed our initial genome-wide association study (GWAS) of 527,869 SNPs on 1,172 individuals with prostate cancer and 1,157 controls of European origin-nested in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial prospective study-by testing 26,958 SNPs in four independent studies (total of 3,941 cases and 3,964 controls). In the combined joint analysis, we confirmed three previously reported loci (two independent SNPs at 8q24 and one in HNF1B (formerly known as TCF2 on 17q); P < 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
738
6
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 845 publications
(786 citation statements)
references
References 28 publications
41
738
6
1
Order By: Relevance
“…Single nucleotide polymorphisms (SNPs) in several genetic loci like 8q24, 22q13 and 17q12 were reported to be linked to PCa susceptibility, early onset of the disease and tumor agressiveness (Al Olama, et al, 2014; Berndt, et al, 2015; Chang, et al, 2009; Cheng, et al, 2009; Eeles, et al, 2009; Eeles, et al, 2013; Gudmundsson, et al, 2009; Helfand, et al, 2015; Levin, et al, 2008; Salinas, et al, 2008; Schumacher, et al, 2011; Takata, et al, 2010; Thomas, et al, 2008; Witte, 2007). Although little is known about the functional aspect of risk SNPs, some studies showed cancer SNPs predominately present in multiple putative regulatory elements (2011; Sille, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in several genetic loci like 8q24, 22q13 and 17q12 were reported to be linked to PCa susceptibility, early onset of the disease and tumor agressiveness (Al Olama, et al, 2014; Berndt, et al, 2015; Chang, et al, 2009; Cheng, et al, 2009; Eeles, et al, 2009; Eeles, et al, 2013; Gudmundsson, et al, 2009; Helfand, et al, 2015; Levin, et al, 2008; Salinas, et al, 2008; Schumacher, et al, 2011; Takata, et al, 2010; Thomas, et al, 2008; Witte, 2007). Although little is known about the functional aspect of risk SNPs, some studies showed cancer SNPs predominately present in multiple putative regulatory elements (2011; Sille, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…9 The MSMB gene is (epi)genetically silenced in PCa. [10][11][12][13] Recently, genome-wide association studies identified a C/T single nucleotide polymorphism rs10993994 in the promoter region of the MSMB gene that correlated with a significantly increased risk of developing PCa. 10,11 The 'TT' genotype, comprising two risk alleles, was associated with a lower expression of the MSMB gene and a severely decreased binding of the transcription factor CREB (cyclic AMP response element-binding protein), which was explained by changes of the CREB-binding site.…”
mentioning
confidence: 99%
“…[10][11][12][13] Recently, genome-wide association studies identified a C/T single nucleotide polymorphism rs10993994 in the promoter region of the MSMB gene that correlated with a significantly increased risk of developing PCa. 10,11 The 'TT' genotype, comprising two risk alleles, was associated with a lower expression of the MSMB gene and a severely decreased binding of the transcription factor CREB (cyclic AMP response element-binding protein), which was explained by changes of the CREB-binding site. 12 In addition, the expression of MSMB is downregulated in PCa by methylation of CpG islands as well as by Polycomb-regulated histone modifications, which are both known to silence genes by making them less accessible to transcription factors.…”
mentioning
confidence: 99%
“…12,[19][20][21][22][23][24] Over 33 loci have been identified that qualify as being genome-wide significant and replicated in more than one study, or internally in multiple validation sets (Supplementary Table 2). The majority of these loci are in intergenic regions, many near known genes, and a few have known biological relevance to PCa.…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%
“…26,27 One of the strongest SNP associations is to the rs10993994 SNP on chromosome 10, in front of the MSMB gene. 21,23,28,29 MSMB encodes beta-microseminoprotein, an immunoglobulin binding factor family protein produced by the epithelial cells of the prostate gland and secreted into the seminal plasma. The MSMB protein has inhibin-like activity and may play a role as an autocrine paracrine factor in uterine, breast and other female reproductive tissues.…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%